The book of pigericks: pig limericks - Lobel, Arnold. (Harper & Row, 1983)
Thirty-eight original limericks about all manner of pigs.
Thirty-eight original limericks about all manner of pigs.
SPEC WALP: In the Lee Walp Family Juvenile Book Collection, Gift of the Lee Walp Family. In dust jacket. Manuscript notes by Lee Walp. Lee Walp's clippings, notes, etc. laid in.
Keywords: Children's poetry, American. / http://id.loc.gov/authorities/subjects/sh85023723; Limericks. / http://id.loc.gov/authorities/subjects/sh85077014; Swine / Juvenile poetry.